The legend of Meneka - Rao, Kritika H. (Rao, Kritika H. Divine dancers duology, 2025)
Across the mortal and immortal realms, celestial dancers known as apsaras are revered for their beauty, allure, and enchanting magic. But Meneka knows that is not all they are. Trained as a weapon, a warrior, Meneka despises leaving each of her marks in thrall to her potent illusions. With every seduction Lord Indra, king of heaven, demands of her for his political gain, she craves her freedom more and more. When a mortal sage's growing powers threaten Indra's supremacy in his own realm, Meneka seizes a rare opportunity. She strikes a deal, if she can seduce this dangerous man, Indra will allow her to forgo future missions. But upon meeting the sage, Kaushika, Meneka finds herself captivated by his energy, ignited by his empathy and passion, even though he threatens everything she's ever known. Can she overthrow the man who is, little by little, stealing her heart, or is Kaushika seducing her instead? As war looms in the skies, Meneka must choose between her duty to protect her home, and the sage who is showing her what true love can mean.